Contrasting antibody responses to intrasubtype superinfection with CRF02_AG. - Colleen R Courtney; Luzia Mayr; Aubin J Nanfack; Andrew N Banin; Michael Tuen; Ruimin Pan; Xunqing Jiang; Xiang-Peng Kong; Allison R Kirkpatrick; Daniel Bruno; Craig A Martens; Lydia Sykora; et al. (PLoS ONE, 2017)
HIV superinfection describes the sequential infection of an individual with two or more unrelated HIV strains. Intersubtype superinfection has been shown to cause a broader and more potent heterologous neutralizing antibody response when compared to singly infected controls, yet the effects of intrasubtype superinfection remain controversial. Longitudinal samples were analyzed phylogenetically for pol and env regions using Next-Generation Sequencing and envelope cloning. The impact of CRF02_AG intrasubtype superinfection was assessed for heterologous neutralization and antibody binding responses. We compared two cases of CRF02_AG intrasubtype superinfection that revealed complete replacement of the initial virus by superinfecting CRF02_AG variants with signs of recombination. NYU6564, who became superinfected at an early time point, exhibited greater changes in antibody binding profiles and generated a more potent neutralizing antibody response post-superinfection compared to NYU6501. In contrast, superinfection occurred at a later time point in NYU6501 with strains harboring significantly longer V1V2 regions with no observable changes in neutralization patterns. Here we show that CRF02_AG intrasubtype superinfection can induce a cross-subtype neutralizing antibody response, and our data suggest timing and/or superinfecting viral envelope characteristics as contributing factors. These results highlight differential outcomes in intrasubtype superinfection and provide the first insight into cases with CRF02_AG, the fourth most prevalent HIV-1 strain worldwide.